Enhancing digital transformation in SMEs : The dynamic capabilities of innovation intermediaries within ecosystems - Hafeez, Shahid; Shahzad, Khuram; De Silva, Muthu (Elsevier, 2025)
While the dynamic capabilities framework discusses the sensing, seizing, and transformation capabilities of organisations, we lack knowledge of the specific dynamic capabilities of intermediaries that support collaborations leading to the digital transformation of small and medium enterprises (SMEs). The specific role of intermediaries supporting collaboration between SMEs and the ecosystem, the unique barriers confronted by SMEs, and the long-term focus required for digital transformation suggest that intermediaries should deploy specific dynamic capabilities. By conducting in-depth interviews with innovation intermediaries, SMEs, and other ecosystem actors in the Ostrobothnia region of Finland, we make three original contributions to the dynamic capability framework. First, while the literature has discussed spotting opportunities and bringing partners together as sensing dynamic capability, we make an original contribution by demonstrating the ‘ancillary opportunity spotting capability’ of intermediaries. This includes intermediaries spotting opportunities to develop digital technologies to address business, environmental, or social challenges of ecosystem actors (e.g. developing carbon-neutral solutions) where SME digital transformation is only indirectly achieved: hence, this is described as an ancillary opportunity. Second, while the literature has discussed that the seizing capability involves exploiting opportunities by using resources, we identified that intermediaries leverage ‘business model co-creation capability’ for seizing. This predominantly consists of them co-creating – with the stakeholders of SMEs (i.e. customers, suppliers, and competitors) – the business models of SMEs for digital transformation. Third, as a transformation capability, intermediaries leverage ‘ecosystem revamping capability’ for continued and scaled-up SME digital transformation, the capabilities associated with which include altering opportunity and ecosystem structures, bridging inter-ecosystem collaborations, and deploying international best practices. Our finding has implications for intermediaries, SMEs, and policymakers keen to enhance SME digital transformation by enabling intermediaries to develop required dynamic capabilities.
Keywords: Intermediaries; Dynamic capabilities; Digital transformation; SMEs; Co-creation; small and medium-sized enterprises; fi=Markkinointi|en=Marketing|; fi=Tuotantotalous|en=Industrial Management|